Capital improvement project evaluation: a hydroelectric generation economic perspective. (23rd April 2015) - Wilson, Reginald
Summary Hydropower is a capital‐intensive energy source with low operations and maintenance (O&M) cost and essentially no fuel costs. Consequently, the levelized cost of energy methodology is a very sensitive component to investment costs and interest rates but less sensitive to economic lifetimes. Because current hydroelectric plants are classified as one of the least costly sources of power generation, there are, however, a wide assortment of site‐specific capital costs and capacity factors. Maintenance activities, predominantly fixed O&M costs, are unjustifiable fundamentals in the capital improvement scheme. The conduct of an explicit aging asset in the hydroelectric generation confines is determined by its previous performance and condition assessment. The asset repair, upgrade, and/or replacement strategies are derived from the documented condition valuations to facilitate specific requirements in the capital improvement program. Moreover, the routine evaluation of the equipment with essential inspections and testing delivers a comprehensive insight of its condition before expensive replacement initiatives are imposed. The application of these evaluation approaches and implements described in this paper are designed to aid the decision‐maker with invaluable information of the equipment condition. Copyright © 2015 John Wiley & Sons, Ltd.